Penerapan Teknik Modelling dan Latihan untuk Meningkatkan Keterampilan Senam Aerobik dan Senam Lantai - Siswanto, Heri (Media Ilmu Keolahragaan Indonesia, 2013)
The purpose of this study to determine whether the application of modeling techniques and exercises to improve skills and gymnastics floor aerobics class 3 K-1 SMK Negeri 1 Waterford in the second semester of the school year 2012/2013.Dalam tests used in data collection techniques to determine student learning outcomes and techniques non-test in the form of sheets of observation by observation to determine the learning process. The research method used was Classroom Action Research to perform two actions in two cycles. From the results of this research note an improvement in learning outcomes and learning processes. From the initial conditions to an increase in cycle 1 average value of 74.77 to 78.83, an increase of 5.43 percent. In the two-cycle is the last cycle the average value is 85.26, which means an increase of 14.03 per cent of the initial conditions. Similarly, the learning process showed an increase in activity and creativity of students and teachers. It can be concluded that the application of modeling techniques and exercises to improve skills and gymnastics floor aerobics class 3 K-1 SMK Negeri 1 Waterford in the second semester of academic year 2012/2013.